Strategi Pengembangan Produksi Budidaya Ikan Lele (Clarias Sp) di Desa Cimuning Kecamatan Mustika Jaya Kota Bekasi - Prakoso, Radianthama Agung Budi; Abubakar, Abubakar; Azzahra, Fatimah (Jurnal Ilmiah Wahana Pendidikan, 2025)
Catfish is one of the most cultivated freshwater fish. Cimuning Village is one of the villages that has potential in the development of catfish production. The purpose of the research is to identify what are internal and external factors and analyze the right catfish production development strategy to increase the income of catfish farmers in Cimuning Village. The methods used are quantitative and qualitative. This research uses primary and secondary data. Primary data collection with observations, interviews and questionnaires. The research respondents were catfish cultivators and stakeholders and were carried out in a purposive manner. The analysis techniques used are analysis of IFAS, EFAS, SWOT Matrix and QSPM Matrix. The results of the analysis show that the internal factors that become strength are quality catfish seeds, the production of their own cultivation development, the cultivators have their own land and are able to create jobs. While the factor that becomes a weakness is the few seed suppliers. Based on external factors, the opportunity is to increase the income of catfish farmers. While the threat factor is competition with fellow catfish farmers. Based on the QSPM matrix, strategic priorities are obtained which are the main alternatives, namely by utilizing market development, their own land potential and human resources with a TAS value of 10.45